(untitled) (Czech Journal of International Relations, 1966)
Before the Second World War, the internationalization of capital took place primarily in the form of international cartels, i.e. contracts of various national monopolies on the economic division of the world, as well as in the form of "participation" in foreign enterprises. Currently, together with participation, the internationalization of capital appears in the form that the production apparatus of certain national monopolies is relocated in other countries and grows into their economy.